When (not) to Look for Contrastive Alternatives: The Role of Pitch Accent Type and Additive Particles. (December 2019) - Braun, Bettina; Asano, Yuki; Dehé, Nicole
This study investigates how pitch accent type and additive particles affect the activation of contrastive alternatives. In Experiment 1, German listeners heard declarative utterances (e.g., The swimmer wanted to put on flippers ) and saw four printed words displayed on screen: one that was a contrastive alternative to the subject noun (e.g., diver ), one that was non-contrastively related (e.g., pool ), the object (e.g., flippers ), and an unrelated distractor. Experiment 1 manipulated pitch accent type, comparing a broad focus control condition to two narrow focus conditions: with a contrastive or non-contrastive accent on the subject noun (nuclear L+H* vs. H+L*, respectively, followed by deaccentuation). In Experiment 2, the utterances in the narrow focus conditions were preceded by the unstressed additive particle auch ("also"), which may trigger alternatives itself. It associated with the accented subject. Results showed that, compared to the control condition, participants directed more fixations to the contrastive alternative when the subject was realized with a contrastive accent (nuclear L+H*) than when it was realized with non-contrastive H+L*, while additive particles had no effect. Hence, accent type is the primary trigger for signaling the presence of alternatives (i.e., contrast). Implications for theories of information structure and the processing of additive particles are discussed.